2005
DOI: 10.1093/jmedent/42.5.719
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Phenotype ofTriatoma dimidiataPopulations and Its Relationship with Species ofphyllosomaandprotractaComplexes

Abstract: Triatoma dimidiata (Latreille 1811) Reduviidae Triatominae is the main vector of Chagas disease in several countries of Latin America. As for other vector species, the characterization of T. dimidiata subpopulations within particular geographical regions or occupying different habitats could help in better planning of vector control actions. A first objective in this study was to evaluate the antennal phenotype as a phenetic marker to characterize populations of T. dimidiata collected in different geographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Studies based on morphometry [51], RAPD [52], antennal sensilla [53] and cuticular hydrocarbons [20], [54] of cave-dwelling specimens from Lanquín, Alta Verapaz, in Guatemala, revealed great phenotypic divergence from all other T. dimidiata populations analyzed. The differentiation was so remarkable that it was suggested that these insects could represent an incipient species [51], [54].…”
Section: Discussionmentioning
confidence: 97%
“…Studies based on morphometry [51], RAPD [52], antennal sensilla [53] and cuticular hydrocarbons [20], [54] of cave-dwelling specimens from Lanquín, Alta Verapaz, in Guatemala, revealed great phenotypic divergence from all other T. dimidiata populations analyzed. The differentiation was so remarkable that it was suggested that these insects could represent an incipient species [51], [54].…”
Section: Discussionmentioning
confidence: 97%
“…This study even revealed differences consistent with a specific status for populations from the Yucatan peninsula, Mexico [4][6], thus opening a debate. A large number of recent, multidisciplinary studies using RAPD-PCR, genital structures, morphometrics of head characters, and antennal phenotypes have shown that variation within this species seems much greater than previously considered [8], [12][16]. Morphometric and cuticular hydrocarbon analyses suggest that a sylvatic population from Lanquin, Guatemala, is undergoing a speciation process [13],[17].…”
Section: Introductionmentioning
confidence: 93%
“…These authors also noted that cave specimens differed from specimens collected outside the caves, similar to other arthropods, with “diminished pigmentation, reduction in size of eyes and ocelli, [and] longer head[s]”; however, a distinct taxonomic group was not suggested for the cave specimens as most of these are well-known environmentally-influenced modifications of cave dwellers. More recent work on antenna structure, head morphometry, and cuticular hydrocarbons has variously clustered T. dimidiata into two to four distinct taxa supporting the identification of unique cave populations, and identifying at least one cryptic species (by cuticular hydrocarbon analysis) (Bustamante et al, 2004; Calderón-Fernández et al, 2005; Calderón-Fernández et al, 2011; Catalá et al, 2005). So phenotypic results suggest one to four taxa.…”
Section: Introductionmentioning
confidence: 95%